2013
DOI: 10.1002/hyp.9931
|View full text |Cite
|
Sign up to set email alerts
|

Observations of late winter Canadian tundra snow cover properties

Abstract: Abstract:Tundra snow cover is important to monitor as it influences local, regional, and global-scale surface water balance, energy fluxes, as well as ecosystem and permafrost dynamics. Observations are already showing a decrease in spring snow cover duration at high latitudes, but the impact of changing winter season temperature and precipitation on variables such as snow water equivalent (SWE) is less clear. A multi-year project was initiated in 2004 with the objective to quantify tundra snow cover propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…The same geostatistical analysis method is therefore performed for snow surface and residual snow depth. We used the geoR package in statistical software R (Ribeiro Jr. and Diggle, 2001; https: //www.r-project.org/).…”
Section: Spatial Variability Analysis Of Topography and Snow Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…The same geostatistical analysis method is therefore performed for snow surface and residual snow depth. We used the geoR package in statistical software R (Ribeiro Jr. and Diggle, 2001; https: //www.r-project.org/).…”
Section: Spatial Variability Analysis Of Topography and Snow Depthmentioning
confidence: 99%
“…Snow depth characterization in Arctic tundra environments has traditionally been performed using snow depth probes (Benson and Sturm, 1993;Hirashima et al, 2004;Derksen et al, 2009;Rees et al, 2014;Dvornikov et al, 2015) or modeled using terrain and vegetation information (Sturm and Wagner, 2010;Liston and Sturm, 1998;Pomeroy et al, 1997). Recently, there have been several new techniques for estimating snow depth in high resolution and in a noninvasive and spatially extensive manner.…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al (1998) and Kitaev et al (2005) showed that higher air temperatures caused an increase in snowfall in winter from 1936 through 1995, and thus greater snow depth was observed in northern Eurasia. Snow depth distribution and variation are controlled by terrain (i.e., elevation, slope, aspect, and roughness) and vegetation Grünewald et al, 2014;Revuelto et al, 2014;Rees et al, 2014;Dickerson-Lange et al, 2015). Snow depth is closely related to synoptic-scale atmospheric circulation indices such as the North Atlantic OscillationArctic Oscillation (NAO/AO).…”
Section: Introductionmentioning
confidence: 99%
“…The costs of snow and ice management alone for the City of Saskatoon reached over $13 million CAD in 2014, but due to unpredictable weather patterns, additional contingency planning was needed as the budgeted finances soon were spent. Amid changing snowfall regimes, there is, thus, a need for better monitoring and provision of scientific support to urban managers for snow services (Brown and Mote 2009;Rees et al 2014). …”
Section: Cities and Snowfallmentioning
confidence: 99%